A2: On assessing and anticipating the consequences of introducing benefit-sharing mechanisms - Quintero, Marcela; Ball, C.; Estrada, R.D. (2009)
This project is about showing whether BSM are effective. It seeks to quantify the consequences of BSM-driven changes in land and water management for livelihoods in upstream rural communities, and for water supplies for downstream water consumers. It will develop methods to anticipate ex ante the likely consequences of introducing BSM as well as monitoring and measuring these consequences ex post. Finally, it will introduce methods for adaptive management in BSM design and planning, so that new instances of BSM can benefit from lessons already learned – for example, so that BSM design is more likely to result in benefits to the upstream rural poor, and to the environment, as well as for downstream water consumers